TRADING BEHAVIOR AND ASSET PRICING UNDER HETEROGENEOUS EXPECTATIONS - Sartono, R. Agus (Gadjah Mada International Journal of Business, 2005)
This research models trading behavior and examines the impact of heterogeneous expectations on asset prices. We extend Kyleâs (1985) one-period model to two-period model. The model shows that the informed trader takes into account not only the private information but also the pricing function. The price is an increasing function of the volatility of the asset value and decreasing in the volatility of uninformed tradersâ demand. The costly information acquisition has an impact on the optimum demand but it has no direct impact on the price.We find the market depth is a linear function of the volatility of the uninformed traders and a weighted average of the total error variance of information. The depth is also decreasing in the volatility of the cash flow innovations. This argument is in line with the second finding, when the volatility of cash flow innovations increases, the value of risky asset becomes more volatile, and as a result the bigger are the advantages of having private information. Our research raises some questions for further investigation. We indirectly assume that the informed traders make a profit at the expense on the uninformed traders. The question is why the uninformed traders willing to face losses? What happen if there are n informed traders who have diverse information?